Characterizing phenotype variants of Cercosporidium personatum, causal agent of peanut late leaf spot disease, their morphology, genetics and metabolites - Renee S. Arias; Emily G. Cantonwine; Valerie A. Orner; Travis E. Walk; Alicia N. Massa; Jane E. Stewart; John T. Dobbs; Atalya Manchester; Pirada S. Higbee; Marshall C. Lamb; Victor S. Sobolev (Scientific Reports)
Abstract Cercosporidium personatum (CP) causes peanut late leaf spot (LLS) disease with 70% yield losses unless controlled by fungicides. CP grows slowly in culture, exhibiting variable phenotypes. To explain those variations, we analyzed the morphology, genomes, transcriptomes and chemical composition of three morphotypes, herein called RED, TAN, and BROWN. We characterized, for the first time in CP, anthraquinone (AQ) precursors of dothistromin (DOT), including averantin, averufin, norsolorinic acid, versicolorin B, versicolorin A, nidurufin and averufanin. BROWN had the highest AQ and melanin (15 mg/g DW) contents. RED had the highest ergosterol (855 µM FW) and chitin (beta-glucans, 4% DW) contents. RED and TAN had higher resistance to xenobiotics (p ≤ 1.0E-3), including chlorothalonil, tebuconazole and caffeine, compared to CP NRRL 64463. In RED, TAN, and BROWN, rates of single nucleotide polymorphisms (SNP) (1.4–1.7 nt/kb) and amino acid changes (3k-4k) were higher than in NRRL 64463. Differential gene expression (p ≤ 1.0E-5) was observed in 47 pathogenicity/virulence genes, 41 carbohydrate-active enzymes (CAZymes), and 23 pigment/mycotoxin biosynthesis genes. We describe the MAT1 locus, and a method to evaluate CP-xenobiotic resistance in 5 days. Chemical profiles indicate each CP morphotype could trigger different immune response in plants, probably hindering development of durable LLS resistance.